College Student Commitment and Outdoor Orientation Programming. (September 2020) - Davidson, Curt; Ewert, Alan
Background: Increasingly colleges and universities are utilizing Outdoor Orientation Programs (OOPs) to help incoming students assimilate into college life. These programs have shown promise in recent analyses for enhancing desired outcomes with particular consideration shown to pro-social behavior and retention outcomes. Purpose: To examine how effective OOPs are in preparing students for a successful college student experience, particularly with variables known to influence student success and commitment to college. Methodology/Approach: Data were collected from four universities across the United States. Participants in this study were 205 undergraduate students from 17 to 25 years old who self-enrolled in their respective institutions OOP. This study used the College Student Readiness Inventory to generate a hypothesis concerning the possible effects of an OOP experience concerning predictive and outcomes variables relative to college student commitment. Findings/Conclusions: Using SmartPLS, the main effects of the OOP indicated predictive relationships between Commitment to College and Goal Striving, Communication Skills, Social Activity, Emotional Reactivity, Study Skills, and Social Connection. Academic Self-Discipline, Academic Self-Confidence, and Self-Determination on Commitment to College. Implications: Study findings suggest specific connections between predicting college student commitment before and after an OOP.